PENGALIHAN DEBITUR DALAM KREDIT PEMILIKAN RUMAH (KPR) MENURUT HUKUM TANAH NASIONAL: Analysis of Debtors Transfer in Housing Loans (KPR) in of National Land Law - Saphira Eka Aprilia; Dyah Setyorini (AMICUS CURIAE, 2024)
Housing Loans (KPR) is a bankprovided facility that allows for the credit-based purchase of real estate and residential buildings, with the real estate and residential buildings serving as mortgage-backed collateral. Decision 81/Pdt.g/2019/PN.Ckr Analysis The question is how the National Land Law is applied to the transfer of debtors in the KPR and how the judge interpreted it decision 81/Pdt.g/2019/PN.ckr in accordance with Law Number4 of 1996 regarding Mortgage Rights onLand and Objects Related to Regulation Number24 of 1997 regarding Land Registration. Normative descriptive research data from literature. Deductive conclusion drawing and qualitative data analysi. The mortgage debtor canbe transferred two ways: first,with the knowledge the bank ascreditor, where the process is the same as applying for bank mortgage, and second, without the knowledge of creditor, through buying and selling transactions supported by proof of receipt. One the judge's considerations is that the process of buying and selling land between the old debtor and the new debtor has been proven that receipt is considered valid; however, the judge's consideration is inappropriate because the transfer of debtor without the creditor's knowledge is included in default, and the creditor can demand compensation and nulland void. Article37 paragraph of Government Regulatiion Number24 of 1997 concerniing Land Registration.